2021
DOI: 10.2147/ppa.s316253
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Medical Follow-Up Adherence for Patients on All-Oral Regimen for Multidrug-Resistant Tuberculosis in Shenzhen, China

Abstract: The aim of this study is to identify factors affecting medical follow-up adherence of pulmonary multidrug-resistant tuberculosis (MDR-TB) patients on an all-oral regimen in Shenzhen, China to enhance intervention measures for increased treatment success. Methods: A cohort study was conducted in The Third People's Hospital of Shenzhen on MDR-TB patients switched to an all-oral regimen to evaluate effectiveness following the WHO's recommendation in late 2018. We recruited patients in the group for an opinion sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In line with our findings, a study conducted in Eastern China showed that patients who were divorced or widowed were more likely to miss medications compared to those who were married (Fang et al, 2019). Similarly, a study in China reported that single patients had difficulties meeting medical appointments and were more likely to default from routine multi-drug resistant (MDR) tuberculosis treatment (Li et al, 2021). In another similar quantitative survey conducted among migrant workers, divorce or being bereft of a spouse was a significant correlate of a non-adherence level of 16% (Zhou et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…In line with our findings, a study conducted in Eastern China showed that patients who were divorced or widowed were more likely to miss medications compared to those who were married (Fang et al, 2019). Similarly, a study in China reported that single patients had difficulties meeting medical appointments and were more likely to default from routine multi-drug resistant (MDR) tuberculosis treatment (Li et al, 2021). In another similar quantitative survey conducted among migrant workers, divorce or being bereft of a spouse was a significant correlate of a non-adherence level of 16% (Zhou et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…One of the biggest challenges of this traditional manner is the long waiting time in the queue to receive services [ 5 ]. A study shows that a non-user friendly appointment system is the main barrier to patients’ medical follow-up compliance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…TB patients have the risk to fall into medication failure, and so do the MDR TB patients because the essence of medication lies in the compliance ( 24 , 25 ). Therefore, MDR TB patients really need support ( 26 ). The reminder via SMS is an effort to maintain the patients' commitment to be able to recover because they know that they are supported at least by this researcher team.…”
Section: Discussionmentioning
confidence: 99%